Factors Influencing Job Satisfaction in Certified Peer Specialists - Grant, Emily A. (International Journal of Psychosocial Rehabilitation, 2013)
The role of Certified Peer Specialist addresses the growing need for mental health services and improves quality of mental health services. In order for CPSs to successfully fulfill their role they must be satisfied with their work setting. This study examines the impact of communal orientation, workplace integration, job activities, personal job history, and demographics on CPS’s job satisfaction. Results indicate CPSs reporting higher organizational support, workplace integration, and a his- tory of lengthy employments report higher job satisfaction than other CPSs. Interestingly, demographic characteristics, sharing personal recovery story, communal orientation and workload did not demonstrate an impact on job satisfaction.